In Darkling Wood - Carroll, Emma (Faber & Faber, 2015)
When Alice's brother gets a longed-for chance for a heart transplant, Alice is suddenly bundled off to her estranged grandmother's house. There's nothing good about staying with Nell, except for the beautiful Darkling Wood at the end of her garden - but Nell wants to have it cut down. Alice feels at home there, at peace, and even finds a friend, Flo. But Flo doesn't seem to go to the local school and no one in town has heard of a girl with that name. When Flo shows Alice the surprising secrets of Darkling Wood, Alice starts to wonder, what is real? And can she find out in time to save the wood from destruction?